Jihad Marriage for ISIS Women in Indonesia - Indra Martian Permana (Cyber Media Indonesia, 2019)
Terrorism in Islam is a legacy of the khawarij ideology that disbelieved and fought with Ali bi Abi Talib RA and the Muslims at that time. Khawarij's ideology then became a terrorism movement in various countries including Indonesia. In 2014, ISIS declared in Syria brought the concept of khawarij with the thought of ghuluw fii takfir which disbelieved anyone who did not support and join the struggle of ISIS. The social impact of ISIS in Indonesia on divorce and marriage caused by ISIS women has the idea of ghuluw fii takfir then disbelieves and divorces her husband who does not join ISIS and then remarries ISIS supporters. Marriage conducted by ISIS women is deformed by Shari'a because it does not involve a marriage guardian. Marriage in Islam is a sacred and holy matter. Islam regulates the rules of marriage so that the function of Maqosid Asy Sharia, namely the maintenance of offspring can be maintained, while for cases of marriage and divorce involving ISIS, there are many things that Islamic rules violate the provisions of the Shari'a. The research method was taken by studying literature and then interviewing various sources. ISIS marriages and divorce studies become studies related to Sharia irregularities in divorce and marriage issues for ISIS women in Indonesia. DOI: https://doi.org/10.5281/zenodo.3467631